Prince Issa Bin Mousa Al-Abbasi and his Role in the Abbasid State during the Period 132-160 HD / 750-776 AD - Shakir, Amna; BenKeira , Nadjib (Al-Adab Journal, 2025)
The early Abbasid era was one of the most prosperous periods in Islamic history, marked by remarkable progress in culture and civilization. This era immortalized significant scientific and historical achievements. The Abbasid caliphs relied on specific individuals for military activity services, as this allocation required specific military skills and competencies that inaccessible to an average civilian. Isa ibn Musa played a major military role in the foundation of the first Abbasid state. This study aims to shed light on the life of Isa ibn Musa al-Abbasi, who demonstrated administrative efficiency and political aptitude during the early Abbasid state, covering the period 132-160 AH / 750-776 AD. Isa ibn Musa left behind great accomplishments in both administrative and military fields, whereas my main focus point in this study is on his military contributions and achievements. He was known as the knight of the Abbasids and their unsheathed sword. He was appointed as the crown prince by Al-Mansur and played a crucial role in securing the early Abbasid state’s prosperity. Isa ibn Musa’s significant military achievements included his efforts to suppress the early revolutionary movements initiated by the Zaydi Shiites, the sons of Abdullah ibn Hasan, who sought to overthrow the Abbasid state, believing themselves to be more worthy of leading the Muslim community. Isa defeated them, resulting in their deaths, and through his efforts, the Abbasid state was consolidated.